Tumor Necrosis Factor-α-Induced Colitis Increases NADPH Oxidase 1 Expression, Oxidative Stress, and Neutrophil Recruitment in the Colon: Preventive Effect of Apocynin - Mouzaoui, Souad; Djerdjouri, Bahia; Makhezer, Nesrine; Kroviarski, Yolande; El-Benna, Jamel; Dang, Pham My-Chan (Mediators of Inflammation, 2014)
Reactive oxygen species- (ROS-) mediated injury has been implicated in several inflammatory disorders, including inflammatory bowel disease (IBD). NADPH oxidases (NOXs) are the major source of endogenous ROS. Here, we investigated the role of NOXs derived-ROS in a mouse model of colitis induced by the proinflammatory cytokine, tumor necrosis factor-α (TNF-α). Intraperitoneal injection of TNFα (10 μg · kg−1) induced an acute inflammation of the colon and a marked increase in expression of NADPH oxidase 1 (NOX1), a colon specific NADPH oxidase isoform. TNFα-induced colitis was also characterized by high production of keratinocyte-derived chemokine (KC) and mucosal infiltration of neutrophils, NOX2-expressing cells. Concomitantly, ROS production and lipid peroxidation were significantly enhanced while catalase activity and glutathione level were reduced indicating a redox imbalance in the colon. Furthermore, the redox-sensitive MAP kinases, ERK1/2 and p38 MAPK, were activated during TNFα-induced colitis. Pretreatment of mice with apocynin, an NADPH oxidase inhibitor with antioxidant properties, before TNFα challenge, prevented all these events. These data suggest that ROS derived from NADPH oxidases (mainly NOX1 and NOX2) and MAP kinase pathways could contribute to the induction and expansion of oxidative lesions characteristics of IBD and that apocynin could potentially be beneficial in IBD treatment.